2009
DOI: 10.1016/j.taap.2008.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Time-course comparison of xenobiotic activators of CAR and PPARα in mouse liver

Abstract: Constitutive androstane receptor (CAR) and peroxisome proliferator activated receptor (PPAR)α are transcription factors known to be primary mediators of liver effects, including carcinogenesis, by phenobarbital-like compounds and peroxisome proliferators, respectively, in rodents. Many similarities exist in the phenotypes elicited by these two classes of agents in rodent liver, and we hypothesized that the initial transcriptional responses to the xenobiotic activators of CAR and PPARα will exhibit distinct pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Activation of CAR in both the mouse and rat results in changes in the expression of a large number of genes involved in phase I and II xenobiotic metabolism, cell proliferation, apoptosis and energy metabolism (Hamadeh et al, 2002; Ross et al, 2009, 2010; Tien & Negishi, 2006; Ueda et al, 2002; Waterman et al, 2010; Yoshinari et al, 2008). Studies in wild-type mice and CAR-knockout mice have demonstrated that not all genes affected by PB are CAR-dependent (Ueda et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of CAR in both the mouse and rat results in changes in the expression of a large number of genes involved in phase I and II xenobiotic metabolism, cell proliferation, apoptosis and energy metabolism (Hamadeh et al, 2002; Ross et al, 2009, 2010; Tien & Negishi, 2006; Ueda et al, 2002; Waterman et al, 2010; Yoshinari et al, 2008). Studies in wild-type mice and CAR-knockout mice have demonstrated that not all genes affected by PB are CAR-dependent (Ueda et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mice and rats have demonstrated that while some hepatic genes are affected by both the CAR activator PB and peroxisome proliferators (which activate PPARα), many other genes are only affected by either PB or peroxisome proliferators (Hamadeh et al, 2002; Ross et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…1B), an average-linkage, hierarchical clustering was performed in R, on mean-centered data (centered by differentially expressed genes, as in [46]), and the output is shown as a heatmap in Supplemental Figure 1. The two major categories of differentially expressed genes – those that are predominantly downregulated over developmental time vs. those that are predominantly upregulated over developmental time - showed only minor differences (ethanol vs. control) from 24 to 36 hpf.…”
Section: Resultsmentioning
confidence: 99%
“…Average-linkage, hierarchical clustering was performed using EDGE software, in the R programming environment. Clusters were built using mean-centered data, and with the correlation distance option, similar to the approach of [46], and displayed using the heatmap function.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, some CAR ligands function as inverse agonists, i.e., reducing the constitutive activity (Forman et al, 1998). Microarray analysis studies have demonstrated that CAR ligands upregulate or repress genes with diverse functions in mouse liver, including genes involved in regulation of energy metabolism and heme synthesis (Rezen et al, 2009; Ross et al, 2009; Slatter et al, 2006; Ueda et al, 2002). Crystallographic structures of human and mouse CARs have provided insight into both the high level of constitutive activity and the ability of steroidal compounds (e.g., androstenol, 5α-androst-16-en-3α-ol) to act as inverse agonists (Shan et al, 2004; Suino et al, 2004; Xu et al, 2004).…”
Section: Evolution Of Nr1h and Nr1i Nuclear Hormone Receptorsmentioning
confidence: 99%